PRINCIPLES OF TRAINING OF MANAGEMENT PERSONNEL FOR PRESCHOOL ORGANIZATIONS - Umarova Muqaddas Muxtorovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article covers the issues of systematic development of scientific and methodical knowledge of future leadership personnel in the process of higher pedagogical education, arming students with the most modern knowledge, implementation of pedagogical process aimed at teaching them the secrets of the art of management.